21 for 21 - Stankosky, Michael; Baldanza, Carolyn R. (Bingley, U.K. : Emerald Publishing Limited, 2018)
Based on over fifty years of experience from the author's hands-on work in the field, Michael Stankosky provides 21 guiding principles on how to lead and manage today's global organization. 21 for 21 is packed with case studies, aiding visuals, and mantras to help facilitate a deeper understanding of the dynamics and complexity of leading and managing a global enterprise, and it is both multi- and inter- disciplinary in its treatment. Each chapter focuses on a different principle: from successful knowledge management, to the secrets of successful negotiations, and managing systems engineering alongside project management. This applicable guide is an ideal companion for MBA students of management, leadership, and innovation, and it is also of keen interest to senior managers and leaders in a global organization, and researchers in these areas.
Includes index.
Includes bibliographical references.
Print version record
Keywords: International business enterprises -- Management; International business enterprises -- Case studies; Business & Economics -- General; Economics, finance, business & management